Analysis of the Serum Bile Acid Composition for Differential Diagnosis in Patients with Liver Disease - Tomonori Sugita; Katsushi Amano; Masanori Nakano; Noriko Masubuchi; Masahiro Sugihara; Tomokazu Matsuura (Gastroenterology Research and Practice)
Objectives. We determined the serum bile acid (BA) composition in patients with liver diseases and healthy volunteers to investigate the relationship between the etiologies of liver disease and BA metabolism. Material and Methods. Sera from 150 patients with liver diseases and 46 healthy volunteers were obtained. The serum concentrations of the 16 different BAs were determined according to the LC-MS/MS method and were compared between the different liver diseases. Results. A total of 150 subjects, including patients with hepatitis C virus (HCV) (n=44), hepatitis B virus (HBV) (n=23), alcoholic liver disease (ALD) (n=21), biliary tract disease (n=20), nonalcoholic fatty liver disease (NAFLD) (n=13), and other liver diseases (n=29), were recruited. The levels of UDCA and GUDCA were significantly higher in the ALD group, and the levels of DCA and UDCA were significantly lower in the biliary tract diseases group than in viral hepatitis group. In the UDCA therapy (−) subgroup, a significantly lower level of TLCA was observed in the ALD group, with lower levels of CDCA, DCA, and GLCA noted in biliary tract diseases group compared to viral hepatitis group. Conclusions. Analysis of the BA composition may be useful for differential diagnosis in liver disease.